Iron man [videorecording (DVD)] - Downey, Robert, Jr., 1965-; Howard, Terrence; Bridges, Jeff, 1949-; Paltrow, Gwyneth, 1972- (Paramount Home Entertainment, 2008)
A wealthy industrialist is held captive in enemy territory and escapes by building a high-tech suit made of armor. When he returns home, he decides to use his money, talents, and suit to save the world. Bonus features include deleted and extended scenes.